2013
DOI: 10.1182/blood-2012-01-406272
|View full text |Cite
|
Sign up to set email alerts
|

Integrin alpha4 blockade sensitizes drug resistant pre-B acute lymphoblastic leukemia to chemotherapy

Abstract: Key Points We evaluated interference with integrin alpha4–mediated stromal adhesion as a new acute lymphoblastic leukemia treatment. Integrin alpha4 blockade using natalizumab in combination with chemotherapy sensitizes pre-B acute lymphoblastic leukemia to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 24 publications
8
134
0
1
Order By: Relevance
“…Notably, a recent report showed dramatic improvement of survival of mice transplanted with primary human ALL cells, on combination of Natalizumab, an antifunctional VLA-4 antibody, with chemotherapy. 45 Our data further indicated that coculture with BM-MSCs can also induce NF-kB activation in leukemia cells ( Figure 5E) and that blockade of the VLA-4-VCAM-1 interaction during coculture can impair levels of IL-1a, and to a less extent IL-1b, mRNA expression in REH and OCI-AML3 leukemia cells ( Figure 5C-D). In addition, disruption of the VLA-4-VCAM-1 interaction during coculture impaired the nuclear translocation of NF-kB in BM-MSC ( Figure 5F).…”
Section: Discussionsupporting
confidence: 68%
“…Notably, a recent report showed dramatic improvement of survival of mice transplanted with primary human ALL cells, on combination of Natalizumab, an antifunctional VLA-4 antibody, with chemotherapy. 45 Our data further indicated that coculture with BM-MSCs can also induce NF-kB activation in leukemia cells ( Figure 5E) and that blockade of the VLA-4-VCAM-1 interaction during coculture can impair levels of IL-1a, and to a less extent IL-1b, mRNA expression in REH and OCI-AML3 leukemia cells ( Figure 5C-D). In addition, disruption of the VLA-4-VCAM-1 interaction during coculture impaired the nuclear translocation of NF-kB in BM-MSC ( Figure 5F).…”
Section: Discussionsupporting
confidence: 68%
“…Increased expression of THY1 (Yamazaki et al, 2009) and integrins (Hsieh et al, 2013; Miller et al, 2013) have been noted previously in ALL and Ikzf1 -mutant mouse B-cells (Joshi et al, 2014) but not in Ph + ALL. In gain- and loss-of-function studies, we have shown that upregulation of these genes is a consequence of IKZF1 alterations and directly contributes to enhanced adhesion and self-renewal properties in Ikzf1- altered BCR-ABL1 cells.…”
Section: Discussionsupporting
confidence: 63%
“…The combination of carboplatin and anti-α4β1 integrin antibodies results in increased ovarian cancer cell death and doubling time in vitro and significantly reduces tumor burden in murine models of platinum-resistant peritoneal disease [155]. Integrin α4 blockade sensitizes resistant human leukemia blasts to acute lymphoblastic leukemia (ALL) chemotherapy (vincristine, dexamethasone, and L-asparaginase) in vitro and its addition to standard ALL chemotherapy prolongs the survival of NOD/SCID recipients of human pre-B ALL cells in vivo [156].…”
Section: Integrins and Cell Adhesion-mediated Drug Resistancementioning
confidence: 99%